Porosity : establishing the relationship between drying parameters and dried food quality /: establishing the relationship between drying parameters and dried food quality. ([2016]) - Joardder, Mohammad U.H; Karim, Azharul; Kumar, Chandan; Brown, Richard J
No abstract available